Advanced Modeling and Simulation of Vehicle Active Aerodynamic Safety - Krzysztof Kurec; Michał Remer; Jakub Broniszewski; Przemysław Bibik; Sylwester Tudruj; Janusz Piechna (Journal of Advanced Transportation)
The aim of this study was to extend the safety limits of fast moving cars by the application, in a controlled way, of aerodynamic forces which increase as the square of a car’s velocity and, if left uncontrolled, dramatically reduce car safety. This paper presents the methods, assumptions, and results of numerical and experimental investigations by modeling and simulation of the aerodynamic characteristics and dynamics of a small sports car equipped with movable aerodynamic elements operated by an electronic subsystem for data acquisition and aerodynamics active automatic control.